Screening Strategies for Colorectal Cancer: A Systematic Review of the Evidence - Robin S McLeod; members of the Canadian Task Force on Preventive Health Care (Canadian Journal of Gastroenterology, 2001)
BACKGROUND: Colorectal cancer is the third most common cancer in Canada. It is well recognized that there are improved survival rates if the disease is treated in its early stages, and indeed this may be a preventable disease. This paper systematically reviews the effectiveness of specific screening techniques for colorectal cancer in asymptomatic individuals at normal or above average risk.